2007
DOI: 10.15666/aeer/0501_165175
|View full text |Cite
|
Sign up to set email alerts
|

Application of Airborne Hype Rspectral and Thermal Images to Analyse Urban Microclimate

Abstract: Jung-Tőkei-Kardeván: Application of airborne hyperspectral and thermal images to analyse urban microclimate APPLIED ECOLOGY AND ENVIRONMENTAL RESEARCH 5(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There is a very interesting possibility to increase the spatial resolution of these images (Jung et al, 2007). Its base is the fact that the NDVI indices highly correlate with the temperature values in some certain regions.…”
Section: Methodsmentioning
confidence: 99%
“…There is a very interesting possibility to increase the spatial resolution of these images (Jung et al, 2007). Its base is the fact that the NDVI indices highly correlate with the temperature values in some certain regions.…”
Section: Methodsmentioning
confidence: 99%
“…While the authors demonstrated the potential to drive temperature‐emissivity separation algorithms using hyperspectral imagery; they also suggested that the results would have been more accurate if done at pixel sizes coarser than the ≈5 m typically associated with airborne hyperspectral data. In another project using airborne hyperspectral data, Jung et al. (2005, 2007) were able to quantify the oasis effect of green space on the summer heat island of Gyöngyös, Hungary.…”
Section: Selected Applicationsmentioning
confidence: 99%
“…In addition to the location and orientation of the different urban objects, urban surface materials have significant influence on the urban micro climate [93]. Among others, Xu et al and Jung et al [63,94] focus on urban micro climate, by combining thermal airborne remote sensing data with hyperspectral data for land cover mapping. Heldens et al [95] used a detailed surface material map derived from airborne hyperspectral data as input for a micro climate model with which information on temperature, humidity, wind speed, etc.…”
Section: Urban Climatementioning
confidence: 99%